Climate change impact on a wine-producing region using a dynamical downscaling approach: Climate parameters, bioclimatic indices and extreme indices - Blanco-Ward, Daniel (2018)
Climate change is of major relevance to wine production as most of the winegrowing regions of the world are located within relatively narrow latitudinal bands with average growing-season temperatures (GSTs) limited to 13–21 C. This study focuses on the incidence of climate variables and indices that are relevant both for climate change assessment and for grape production, with emphasis on grapevine bioclimatic indices and extreme events (e.g., cold waves, storms, heatwaves). Dynamical downscaling of European Reanalysis-Interim and Max Planck Institute Earth System low-resolution global simulations forced with a Representative Concentration Pathway 8.5 (RCP8.5) greenhouse gas emission scenario was performed with the Weather Research and Forecast (WRF) model to a regional scale including the Douro Valley of Portugal for recent-past (1986–2005) and future periods (2046–2065, 2081–2100). The number, duration and intensity of events were superimposed over critical phenological phases estimated by using a specific local grapevine varietal phenological model in order to assess their positive or negative implications for wine production in the region. An assessment of the relevance of climate parameters and indices and their progression in recent-past and future climate scenarios with regard to the potential impact on wine production was performed. Results indicate a positive relation between higher growing-season heat accumulations and greater vintage yields. A moderate incidence of very hot days (daily maximum temperature above 35 C) and drought from pre-véraison phenological conditions have a positive association with vintage ratings. However, the mid- and long-term WRF-MPI RCP8.5 future climate scenarios reveal shifts to warmer and drier conditions, with the mean GST not remaining within range for quality wine production in the long-term future climate scenario. These results indicate potential impacts that suggest a range of strategies to maintain wine production and quality in the region.